问题 解答题
解方程.
x+
5
9
=
17
18
x+
5
6
=
11
12
6
7
-x=
1
6
2
3
+x=
7
9
7
8
-x=
3
4
0.48x+12=48.
答案

(1)x+

5
9
=
17
18

x+

5
9
-
5
9
=
17
18
-
5
9

x=

7
18

(2)x+

5
6
=
11
12

x+

5
6
-
5
6
=
11
12
-
5
6

x=

1
12

(3)

6
7
-x=
1
6

6
7
-x+x=
1
6
+x,

1
6
+x=
6
7

1
6
+x-
1
6
=
6
7
-
1
6

x=

29
42

(4)

2
3
+x=
7
9

2
3
+x-
2
3
=
7
9
-
2
3

x=

1
9

(5)

7
8
-x=
3
4

7
8
-x+x=
3
4
+x,

3
4
+x=
7
8

3
4
+x-
3
4
=
7
8
-
3
4

x=

1
8

(6)0.48x+12=48,

0.48x+12-12=48-12,

0.48x=36,

0.48x÷0.48=36÷0.48,

x=75.

单项选择题 A1型题
单项选择题